2017
DOI: 10.1371/journal.pone.0180879
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of zinc on cadmium-induced cytotoxicity in chronic inflammation

Abstract: ObjectivesZinc (Zn) has major effects on immune system activation while Cadmium (Cd) has anti-inflammatory and anti-proliferative effects in several chronic inflammatory contexts. The aim of this work was to investigate by which mechanisms Zn could compete with Cd and eventually counteract its deleterious effects. Rheumatoid arthritis (RA) synoviocytes exposed to cytokines were used as a model of chronic inflammation; osteoarthritis (OA) synoviocytes were used as control.MethodsCell/medium fractionation consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…The elevation of serum cytokine levels in rats treated with Cd in our study is in agreement with previous reports (Bonaventura et al 2017;Markiewicz-Górka et al 2019). These results suggested that exposure to Cd stimulates the cytokines production leading to cellular immune response disorders and all of these disturbances are consequences of the oxidative damage of Cd (Bonaventura et al 2017;Turley et al 2019). These results also con rmed that Cd affects the macrophages M1-type which is accountable for the in ammatory response via the releasing of the pro-in ammatory cytokines (Saqib et al 2018).…”
Section: Discussionsupporting
confidence: 94%
“…The elevation of serum cytokine levels in rats treated with Cd in our study is in agreement with previous reports (Bonaventura et al 2017;Markiewicz-Górka et al 2019). These results suggested that exposure to Cd stimulates the cytokines production leading to cellular immune response disorders and all of these disturbances are consequences of the oxidative damage of Cd (Bonaventura et al 2017;Turley et al 2019). These results also con rmed that Cd affects the macrophages M1-type which is accountable for the in ammatory response via the releasing of the pro-in ammatory cytokines (Saqib et al 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Results show a reduction of IL-6 production by synergistic action between IL-17 and TNF-α with no induction of local inflammation and limited deposition of Cd in the liver suggesting a safe risk/benefit ratio without inducing toxic effects on other organs [77]. Further to this study, it was demonstrated that the anti-inflammatory effect of Cd on the synoviocytes was reversed by the presence of zinc that competes with Cd for the non-selective transporter, ZIP-8 [78]. An early human study suggested that Cd may hold anti-inflammatory properties such that the metal suppresses inflammation by downregulating pro-inflammatory genes and thereby inhibiting infiltration into the vessel wall [79] [80].…”
Section: Cadmium-induced Cytokine Releasesupporting
confidence: 55%
“…α2AP expression increased while MMP-3/TIMP-1 ratio decreased in SSc dermal fibroblasts. Bonaventura et al (24) reported that the ratio of MMP-3/TIMP-1 indicates the activity of MMP-3. Hence, we next assessed α2aP expression and MMP-3/TIMP-1 ratio in normal human and SSc dermal fibroblasts by western blotting (normal fibroblasts: n=4, SSc fibroblasts: n=7).…”
Section: Resultsmentioning
confidence: 99%